Level of Learning Organization Practices in Two Primary Schools in the Central Melaka District, Melaka - Ahmad, Nor Hafiza; Kudus, N.; Ahmad, S.S.S. (Journal of Social Transformation and Regional Development, 2023)
This preliminary study was conducted to see the level of learning organization (LO) practice in two primary schools in the district of Melaka Tengah, Melaka. Both schools were selected based on Ujian Pencapaian Sekolah Rendah (UPSR) 2019 School Average Grade (GPS). The questionnaire instrument used in this study was modified from the Learning Organization Practices Profile (LOPP) instrument developed by O’Brien, 1994 and conducted on 60 respondents from two different schools. The overall questionnaire reliability analysis gave a Cronbachâ€™s alpha scale of 0.78. Study data were analyzed using Statistical Package for Social Science (SPSS) For Windows 25 program with descriptive analysis. The findings of this study show that the most dominant LO practice is the system and structure aspects of work, followed by staff development and performance and the lowest is the leadership aspect. The results of the overall study show that the level of LO practice in the schools studied is still at a weak level.